Productivity enhancement of chickpea (Cicer arietinum) through improved production technologies on farmer's field - SINGH, RUDRASEN (The Indian Journal of Agricultural Sciences, 2016)
Sowing time and variety are two important factors which influence crop performance including chickpea. A field experiment was conducted at KVK Chhatarpur Madhya Pradesh winter-sown season of 2007-08 and 2011-12 to find out effect of sowing dates and weed management on weed growth, yield attributes, yield and nutrient uptake by weeds and chickpea (Cicer arietinum L.) under rainfed and irrigated conditions . Front line demonstrations were conducted on 92 farmers' field, to demonstrate production potential and economic benefit of improved technologies comprising wilt resistant varieties (JG 130, JG 11, JG 16 and JG 14), line sowing (40 × 10 cm), integrated nutrient management (20:60:40, NPK kg/ha). The seeds were treated with Trichoderma viride @ 4g/kg seed than inoculated with rhizobium and phosphate-solubilzing bacteria each @ 20 g/kg of seeds. Pre-emergence application of weedicide Pendimethalin @ 1 kg a.i /ha used for effective control of the weeds during rabi season of 2007-08 to 2011-12 in rainfed and irrigated condition .The improved technology recorded a mean yield of 16.00 q/ha which was 30.60% higher then that obtained with farmers' practice yield of 9.68 q/ha. The improved technologies resulted higher mean net income of Rupees 29 302/ha with a benefit cost ratio of 4.13 as compared to local practice (20 490/ha, 3.51). Irrespective of different sowing date of JG-11 chickpea variety, produced highest seed , no. of capsules/plan, no. of seeds/capsule and 100 seed weight(g) (18-22 October, 2008-09) as compared to other dates of sowing.